2017
DOI: 10.1213/xaa.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neuropathy Following Spontaneous Retroperitoneal Hemorrhage After Cardiac Surgery

Abstract: A woman underwent ascending aortic aneurysm repair, aortic root and valve replacement, and coronary artery bypass grafting. Her postoperative course was complicated by stroke and status epilepticus. With supportive care and antiepileptics, her neurologic status improved. Intravenous heparin and aspirin were initiated. On postoperative day 13, she developed a large retroperitoneal hematoma with femoral neuropathy. Because her hematoma was not amenable to percutaneous drainage or surgical evacuation, and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Conservative management is discouraged by some researchers in severe cases [1,[2][3][4][5]. Some authors suggest that the haematoma should be percutaneously drained under CT or US guidance in order to reverse the pressure-induced nerve ischaemia [2][3][4][5]. This possibility was addressed to our radiology department but was soon rejected, as it was suggested that the haematoma was already organized and a CT aspiration would, therefore, be ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conservative management is discouraged by some researchers in severe cases [1,[2][3][4][5]. Some authors suggest that the haematoma should be percutaneously drained under CT or US guidance in order to reverse the pressure-induced nerve ischaemia [2][3][4][5]. This possibility was addressed to our radiology department but was soon rejected, as it was suggested that the haematoma was already organized and a CT aspiration would, therefore, be ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility was addressed to our radiology department but was soon rejected, as it was suggested that the haematoma was already organized and a CT aspiration would, therefore, be ineffective. Open surgical debridement has also been described as a managing option depending on the severity of the femoral neuropathy and the size of the haematoma [1,4,5]. In cases of haemodynamic instability, blood transfusion and crystalloid administration may be required [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations